Corrective Physical Education - Rathbone, Josephine Langworthy (Philadelphia : Saunders, 1948)
This guide, prepared to assist students who have postural and other remedial defects, is divided into four sections. Section one outlines the organization and administration of a remedial physical education program and gives information concerning the administration of alignment tests and corrections. Section two discusses anteroposterior deviations of the cervical region and illustrates 11 basic corrective exercises. Section three describes deviations of the dorsal and lumbar regions of the spine and gives some common causes for these defects. Thirteen corrective exercises are illustrated. Section four discusses the deviations of the legs and feet and illustrates 10 exercises. Eight points to remember are presented. A glossary of related terms and a two-page bibliography are included. (PD)
Includes bibliographical references and index.
Microfiche.
Keywords: Exercise (Physiology); Physical Characteristics; Guides, General